The effects of accompanying sinonasal pathologies on the success of primary dacryocystorhinostomy (Annals of Medical Research, 2022)
Aim: In this study, the results of patients who underwent primary endoscopic endonasal dacryocystorhinostomy surgery and nasolacrimal silicone tube intubation (PEEDCR + NSTI) due to chronic dacryostenosis were evaluated retrospectively. The sinonasal pathologies accompanying these cases and their results were reviewed in the light of the literature.Materials and Methods: The medical records of 55 patients who admitted to State Hospital Ear Nose and Throat Clinics between January 1, 2015 and December 31, 2019, were diagnosed with chronic dacryostenosis and underwent PEEDCR + NSTI surgery were retrospectively examined.Results: Fifty-five patients were included in the study. Thirty-three of the patients (60%) were female and 22 were male (40%). Endoscopic endonasal DCR and nasolacrimal silicon tube intubation were applied to a total of 55 patients, 21 (38.18%) right eye and 34 (61.82%) left eye. Simultaneously, sinonasal pathology surgery was performed on 32 patients. 47 patients (85.5%) achieved complete recovery, while the complaint of eight patients (14.5%) continued.In our study, we found the success rate as 85.5% in primary cases. Nasal revision surgery and EEDCR + NSTI were applied to 8 patients with recurrence. While 7 of these are fully recovered, 1 patient relapsed again. Success rate after revision surgery increased to 98.2%. All of the 8 patients with recurrence were those who underwent sinonasal pathology surgery simultaneously.Conclusion: PEEDCR + NSTI surgery is a functional treatment method that is well-tolerated and with high success in patients with lacrimal stenosis. Sinonasal pathologies were responsible for recurrences. Simultaneously, intranasal pathologies must be treated effectively.
Keywords: Endoscopic dacryocystorhinostomy; Dacryostenosis; Silicone tube; Sinonasal pathologies